Comparison of two new digester designs for bio-gas production using cattle dung as substrate - CHINTU RAVISHANKAR, JOHN ABRAHAM S.B. JYOTHI (Indian Journal of Animal Production and Management, 2019)
Traditional bio-gas digesters like floating drum and fixed dome were compared with two new digesterdesigns, horizontal and vertical flow type, for their efficiency in bio-gas production using cattle dungas substrate. The result obtained showed that; the horizontal flow type digester had maximum bio-gasproduction efficiency in comparison to all other digesters. The bio-gas production in horizontal flow typedigester was significantly (p< 0.001) higher than vertical flow type and old models like floating drum andfixed dome type digesters.